THE IMPACT OF GREEN ECONOMY DEVELOPMENT IN THE REPUBLIC OF UZBEKISTAN ON SUSTAINABLE ECONOMIC GROWTH - Khudoyorov Azizbek Avaz o’g‘li, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article analyzes the impact of green economy development in the Republic of Uzbekistan on sustainable economic growth based on macroeconomic and sectoral indicators. The main purpose of the study is to identify the mechanisms through which green economy factors influence the quality of economic growth, resource efficiency, and environmental sustainability. The article examines the interrelationship between energy efficiency, renewable energy sources, water-saving technologies, ESG standards, green infrastructure, investment activity, and economic growth. The  author substantiates the green economy not as a separate environmental direction detached from economic growth,  but as an essential structural factor determining the quality of economic development. The macroeconomic and sectoral  indicators formed in the Republic of Uzbekistan in 2025 are analyzed in close connection with green economy measures  and reforms. The scientific novelty of the research lies in revealing the impact of the green economy on sustainable  economic growth as a systemic mechanism integrating energy security, efficient use of water resources, industrial  modernization, ESG standards, and green investments.